Slowdown in immigration, labor shortages, and declining skill premia - Federico S. Mandelman; Yang Yu; Francesco Zanetti; Andrei Zlate (Federal Reserve Bank of Atlanta, 2024)
We document a slowdown in low-skilled immigration that began around the onset of the Great Recession in 2007, which was associated with a subsequent rise in low-skilled wages, a decline in the skill premium, and labor shortages in service occupations. Falling returns to education also coincided with a decline in the educational attainment of native workers. We then develop and estimate a stochastic growth model with endogenous immigration and training to rationalize these facts. Lower immigration leads to higher wages for low-skilled workers but also to higher consumer prices and lower aggregate consumption. Importantly, the decline in the skill premium reduces the incentive to train native workers and hurts aggregate productivity over time, which reduces welfare. We assess the implications of stimulus policies implemented during the COVID-19 pandemic and show that the shortage of low-skilled immigrant labor amplified the increase in consumer prices, partially eroding the effectiveness of stimulus.
Keywords: F16; F22; F41; 330; international labor migration; skill premium; task upgrading; heterogeneous workers